Corruption Eradication in Four Asian Countries: A Comparative Legal Analysis - Mahendra, Januar Rahadian; Edwin Setiawan; Hellend , Arbend Ficasso Van (CV. Ius et Ambientis, 2024)
Corruption has both direct and indirect impacts on various sectors. Therefore, anti-corruption efforts are needed in each country to eradicate it. This study discusses the problem of corruption law enforcement in Indonesia by comparing it with Hong Kong, Singapore, and South Korea. The selection of these countries is based on their similarities in having anti-corruption institutions and a long history of corruption as a result of colonialism. This study uses a normative legal method supported by data to produce comprehensive research. The discussion in this study is divided into two, namely by providing a general overview of corruption law enforcement in each country and the problem of law enforcement in Indonesia by comparing it with Hong Kong, Singapore, and South Korea. Based on this study, it can be seen that Indonesia still has complex and systemic problems so that its corruption law enforcement is still weak. The problems that occur include weak political will, corruption eradication that still focuses on the public sector, conflicts of interest between law enforcement agencies, intervention by political elites, criminalization of law enforcers, weak independence, and the absence of supporting laws, a culture of gratification that is still deep-rooted